Hydrogen with water addition: an exergy analysis of the internal combustion engine - Rrustemi, D. N.; Ganippa, L. C.; Axon, C. J. (Frontiers in Mechanical Engineering, 2025)
The internal combustion engine is likely to be used for on- and off-road vehicles for many years yet, but the push to cease using fossil fuels is strong. Hydrogen is a possible alternative fuel with both advantages and disadvantages, so understanding and quantifying the efficiency losses of burning hydrogen are important. The limits to efficiency and the compromises needed to reduce losses can be investigated using exergy analysis. This analysis of a boosted lean-burn neat hydrogen spark ignition engine investigates exergetic processes under real-world engine operating conditions. Using a two-zone combustion model to study in-cylinder processes, the results suggest exergy transfer to work improves with increasing air dilution by diverting exhaust exergy to reversible work. Injecting water could potentially control emissions through in-cylinder thermo-physical property changes. For an equivalence ratio of 0.45 with 5% water addition, the exergy transfers to heat and work decrease by 12% and 7%, respectively. Conversely, the exergy transfers to combustion-related irreversibility and exhaust rise by 2% and 81%, respectively. However, it was shown that increasing manifold air pressures and compression ratios increases the quantity of exergy directed to work and heat, while reducing exergy expelled to exhaust. This exergy analysis of a hydrogen-fueled spark ignition engine operating under real-world parameters shows the need to optimize water injection as the trade-off between engine performance and emission reductions. Understanding the fundamentals of the thermodynamic mechanisms of work loss may inform engineering improvements to minimize exergy losses and increase efficiency and work output.